2016
DOI: 10.3310/phr04060
|View full text |Cite
|
Sign up to set email alerts
|

Bristol Girls Dance Project: a cluster randomised controlled trial of an after-school dance programme to increase physical activity among 11- to 12-year-old girls

Abstract: BackgroundMany children do not meet UK physical activity (PA) guidelines. Girls are less active than boys, and the age-related decline in activity is steeper for girls. Dance is the favourite form of PA among adolescent girls in the UK. Participation in after-school dance classes could significantly contribute to girls’ PA. Therefore, after-school dance may be effective for increasing PA levels.ObjectivesTo determine the effectiveness and cost-effectiveness of a dance-based intervention to increase the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 92 publications
(169 reference statements)
0
21
0
Order By: Relevance
“…The community-recommended response actions include the need for activities that increase access to healthier food, exercise, and weight loss programs [ 32 ]. Like other after-school programs that promote nutritional eating guidelines, we have demonstrated that attendance at structured nutrition education and physical activity hours is associated with reducing BMI Z-scores [ 21 24 ]. Unlike other studies that focus on after-school programming among the more general population, in low-income youth, or in ethnic minority populations, we have demonstrated a positive behavior change trend in a predominantly overweight and obese cohort of impoverished minority youth most at risk for future health disparities.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The community-recommended response actions include the need for activities that increase access to healthier food, exercise, and weight loss programs [ 32 ]. Like other after-school programs that promote nutritional eating guidelines, we have demonstrated that attendance at structured nutrition education and physical activity hours is associated with reducing BMI Z-scores [ 21 24 ]. Unlike other studies that focus on after-school programming among the more general population, in low-income youth, or in ethnic minority populations, we have demonstrated a positive behavior change trend in a predominantly overweight and obese cohort of impoverished minority youth most at risk for future health disparities.…”
Section: Discussionmentioning
confidence: 86%
“…Unlike other studies that focus on after-school programming among the more general population, in low-income youth, or in ethnic minority populations, we have demonstrated a positive behavior change trend in a predominantly overweight and obese cohort of impoverished minority youth most at risk for future health disparities. A majority of the reviewed studies focused on youth in less disadvantaged communities, and although youth with minorities were studied, they had lower rates of overweight and obesity [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding subject recruitment, the Loozit ® study reported difficulty recruiting subjects, with only a 32% success rate per inquiry [37]. Despite improving girls’ physical activity levels, the Bristol Girls Dance Project found retention difficult as attendance steadily declined [38,39]. Still, encouraging dance as exercise is likely motivating and beneficial for girls.…”
Section: Discussionmentioning
confidence: 99%
“…During the refresher training, walk leaders will have the opportunity to practice leading a walk and they will be provided with feedback on pace, route and social engagement. The walk leader training is theoretically underpinned by SDT and similar to the Bristol Girls Dance Project [70], the training facilitator will adopt an autonomy-supportive teaching style that strengthens walk leaders' personal resources. Walk leaders will be encouraged to decide the format of the walks for example, the use of music or games and routes taken.…”
Section: Randomisationmentioning
confidence: 99%